Seismic Behaviour of Straight-Tenon Wood Frames with Column Foot Damage - Shengcai Li; Zhijun Jiang; Hongzhen Luo; Lei Zhang (Advances in Civil Engineering)
Timber buildings might incur damages after a long service, because column foot damage affects the structural performance under the continued use. In this paper, six straight-tenon joint wood frame specimens were prepared with varying degrees of two different damage conditions at a scale of 1 : 3.52. To obtain failure mode and hysteresis performance of the specimens, the low-cycle reciprocating loading test was conducted. The stiffness degradation curves and equivalent viscous damping curves of the damaged wood frames were also analysed. The mechanical characteristics of the wood frames with column foot damage under the low-cycle reciprocating load were then simulated using the finite element method, and the results were compared to the test results. It is determined that as the degree of column foot damage increases, the fullness and peak of the hysteresis curves for wood frames, the equivalent viscous damping coefficients, and the overall seismic behaviour of the wood frame all gradually decrease. The skeleton curves obtained by finite element analysis and tests showed good agreement, verifying the influence of column foot damage on the seismic behaviour of ancient wood frame structures.